Knowledge Organization in the Context of Postmodernity from the Theory of Classification Perspective - Pando, Daniel Abraao [UNESP]; Almeida, Carlos Candido de [UNESP] (Ergon-verlag, 2016)
This paper addresses issues related to knowledge organization (KO) in the context of postmodernity from the theory of classification perspective. The methodology is a bibliographic analysis of the representation of these issues, and in relation to modernity, in the Brazilian and international literature. It was possible to verify that: a) while in the modern context there is the idea that classification can be a neutral and objective mirror of the universe of knowledge, the postmodern theory rejects such hypothesis moving its focus on the social praxis and the community language; b) while the modern classification aimed to represent the universe of knowledge, the postmodern classification aims to provide a pragmatic tool for specific domains; and, c) if classification in modernity focused on KO due to the physicality of documents, with the advent of new technologies and a new space of production of digital information, studies related to classification seem to be displaced. We identify a trend in the area where studies on indexing can take a very important part in this context.
Keywords: knowledge organization; classification; postmodernity; modernity; contexts